2007
DOI: 10.1103/physrevlett.99.130502
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Brachistochrone Problem and the Geometry of the State Space in Pseudo-Hermitian Quantum Mechanics

Abstract: A non-Hermitian operator with a real spectrum and a complete set of eigenvectors may serve as the Hamiltonian operator for a unitary quantum system provided that one makes an appropriate choice for the defining inner product of the physical Hilbert state. We study the consequences of such a choice for the representation of states in terms of projection operators and the geometry of the state space. This allows for a careful treatment of the quantum Brachistochrone problem and shows that it is indeed impossible… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
116
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(127 citation statements)
references
References 33 publications
8
116
0
3
Order By: Relevance
“…The arbitrarily short alternative complex pathway from an up state to a down state, as illustrated by this thought experiment, is reminiscent of the short alternative distance between two widely separated space-time points as measured through a wormhole in general relativity. This comparison is of course controversial, and it has subsequently motivated much research and it has generated a lively debate in the literature [2,15,33,35,36,49,52,53,56]. We emphasise that the entire package of flipping the spin is not realised by a unitary operation.…”
Section: Extension Of Non-hermitian Hamiltonians To Higher-dimensmentioning
confidence: 99%
“…The arbitrarily short alternative complex pathway from an up state to a down state, as illustrated by this thought experiment, is reminiscent of the short alternative distance between two widely separated space-time points as measured through a wormhole in general relativity. This comparison is of course controversial, and it has subsequently motivated much research and it has generated a lively debate in the literature [2,15,33,35,36,49,52,53,56]. We emphasise that the entire package of flipping the spin is not realised by a unitary operation.…”
Section: Extension Of Non-hermitian Hamiltonians To Higher-dimensmentioning
confidence: 99%
“…Sem perda de generalidade pode-se descrever todo sistema quântico com matrizes hermitianas. Uma demonstração matematicamente formal desta afirmação pode ser encontrada em [17]. Nesse artigo concluímos que o efeito de transição entre estados quânticos de maneira mais rápida que mecânica quântica usual apenas se trata de uma interpretação equivocada do comportamento dos estados.…”
Section: Conclusãounclassified
“…The notion of pseudo-Hermiticity has also been introduced [21][22][23][24] and it has been shown that every Hamiltonian with a real spectrum is pseudo-Hermitian [25]. 2 More types of pseudo-Hermitian Hamiltonians have also been studied (see [27][28][29][30][31][32][33][34][35][36][37] and references therein). 2 A Hamiltonian H is said to be pseudo-Hermitian if its adjoint H † satisfies H † = η + Hη −1 + , where η + is a positive-definite (metric) operator.…”
Section: Non-hermitian Pt -Symmetric Hamiltoniansmentioning
confidence: 99%